Pengaruh Lama Perendaman Sabut Kelapa sebagai Media Tanam Hidroponik terhadap Pertumbuhan Tanaman Kangkung (Ipomoea reptans) - afrahamiryano afrahamiryano (Eduscience Development Journal, 2019)
Kale (Ipomoea reptans) is a type of vegetable that is widely cultivated in the territory of Indonesia. These vegetables can be processed in various ways, so they are widely consumed by the community. Water spinach cultivation was formerly carried out in water or land areas. However, along with the rapid growth in population and the lack of land that can be used as an agricultural area. New innovations are being made to continue to increase the productivity of vegetable crops without having to use large tracts of land. One method of farming that does not require large areas is hydroponics. Hydroponics is a method of farming using water planting media and materials that are porous (absorb water). One material that can be used is coconut coir waste. This study aims to determine the effect of soaking time for coconut husk as a hydroponic growing media on the growth of water spinach (Ipomoea reptans). This research is a preliminary study using the RKLT (Randomized Complete Group Design) experimental method using 3 repetitions and 3 treatments, namely: (a) without immersion; (b) immersion for 1 x 24 hours; (c) immersion for 2 x 24 hours. Each treatment planted 30 plants and 10 plants per treatment used as sample plants. Observation parameters included the length of time of germination, many seeds that grow per pot, and number of leaves. The hypothesis of this study is that there is an effect of soaking time for Coconut Fiber as a Hydroponic Planting Media on the Growth of Kale (Ipomoea reptans). Based on the results of data analysis. It can be concluded that there is an effect of soaking time for Coconut Fiber as a Hydroponic Planting Media on the Growth of Kale (Ipomoea reptans).